Mortality Outcomes Associated with Blood Group O Versus Non-O in Patients Undergoing Coronary Artery Bypass Grafting - Oktaliansah, Ezra; Maskoen, Tinni T.; Oey, Bernadeth; Suwarman, Suwarman; Pradian, Erwin; Zulfariansyah, Ardi (Jurnal Anestesi Perioperatif, 2026)
Background: Coronary artery bypass grafting (CABG) carries an operative mortality of 1–7%. Von Willebrand factor (vWF) levels are approximately 30% lower in individuals with blood group O compared to non–O groups, potentially influencing post–CABG mortality. This study aimed to compare mortality between blood group O and non–O in adult patients after on–pump CABG in the ICU.Methods: A retrospective cohort study was conducted using secondary data from medical records of adult patients (>18 years) who underwent elective on–pump CABG in the ICU at Dr. Hasan Sadikin General Hospital, Bandung. A sample of 64 patients was required, with a 28–day follow–up post–CABG. Data were analyzed using unpaired t–tests, Mann–Whitney tests, Chi–square, and Fisher’s exact tests, with significance set at p<0.05, using SPSS version 26.0.Results: A total of 129 patients were included, comprising 64 patients with blood group O and 65 with non–O blood groups. Mortality in blood group O patients was 10.9% (7/64), compared with 29.2% (19/65) in non–O patients, a significant difference (p=0.010). Non–O blood group patients had nearly three times higher risk of mortality compared to those with blood group O.Discussion: The observed mortality differences are related to variations in vWF and factor VIII levels among blood groups. Lower vWF levels in blood group O may provide a protective effect against macro–thrombosis in coronary grafts, whereas higher factor VIII levels in non–O groups increase the risk of microvascular thrombosis and secondary myocardial ischemia after on–pump CABG.Conclusion: Adult patients undergoing on–pump CABG with non–O blood groups experience significantly higher mortality compared to those with blood group O. Blood group may be associated with postoperative mortality. However, its role as an independent prognostic factor requires further investigation.